Manufacturer Liability for Harms Caused by Consumers to Others - Hay, Bruce; Spier, Kathryn E (American Economic Review, 2005)
Should the manufacturer of a product be held legally responsible when a consumer, while using the product, harms someone else? We show that if consumers have deep pockets, then manufacturer liability is not desirable. If homogeneous consumers have limited assets, then the best rule is “residual-manufacturer liability” where the manufacturer pays the shortfall in damages not paid by the consumer. Residual-manufacturer liability distorts the market quantity when consumers' willingness to pay is correlated with their propensity to cause harm. It distorts product safety when consumers differ in their wealth levels. In both cases, consumer-only liability may be preferred.